2016
DOI: 10.1039/c6nr05872h
|View full text |Cite
|
Sign up to set email alerts
|

DNA-templated silver nanoclusters: structural correlation and fluorescence modulation

Abstract: 12 years after the introduction of DNA-templated silver nanoclusters (DNA-AgNCs), exciting progress has been made and yet we are still in the midst of trying to fully understand this nanomaterial. The prominent excellence of DNA-AgNCs is undoubtedly its modulatable emission property, of which how variation in DNA templates causes emission tuning remains elusive. Based on the up-to-date DNA-AgNCs, we aim to establish the correlation between the structure/sequence of DNA templates and emission behaviour of AgNCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 122 publications
0
91
0
Order By: Relevance
“…12 In particular, silver nanoclusters (AgNCs) are of interest, and these systems involve stabilizing ligands to prevent them from oxidation and aggregation. 13 Dendrimers, synthetic polymers, biopolymers, thiol ligands, and inorganic matrices have been used as the stabilizing ligands for AgNCs. 6,11,[14][15][16][17] In 2004, Dickson and coworkers first discovered the formation of DNA-templated Ag nanoclusters (DNA-AgNCs) where they showed that DNA acts as a template for the time-dependent and size-specific formation of nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In particular, silver nanoclusters (AgNCs) are of interest, and these systems involve stabilizing ligands to prevent them from oxidation and aggregation. 13 Dendrimers, synthetic polymers, biopolymers, thiol ligands, and inorganic matrices have been used as the stabilizing ligands for AgNCs. 6,11,[14][15][16][17] In 2004, Dickson and coworkers first discovered the formation of DNA-templated Ag nanoclusters (DNA-AgNCs) where they showed that DNA acts as a template for the time-dependent and size-specific formation of nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7]14,[23][24][25][26] The emission tunability can also be altered through experimental conditions, 19,20,27,28 but changing the DNA template itself is considered superior due to the higher functionality in the DNA-AgNCs through emission tuning. 13 Various research groups have conducted extensive experimental investigations on DNA-AgNCs. Many studies have been performed to understand the effects from the DNA base pairs on the small AgNCs (∼Ag 2 -Ag 30 ) 18,[29][30][31][32] and some provide insights into creating AgNCs using different DNA platforms.…”
Section: Introductionmentioning
confidence: 99%
“…
formation of AgNC and tune the size and fluorescent properties of AgNC. [23][24][25] Many DNA structures have been employed to prepare DNA/AgNC, such as single-stranded DNA (ssDNA), [26][27][28] double-stranded DNA (dsDNA), [29][30][31] and triple-stranded DNA (tsDNA) [32] . As an artificial DNA nanoarchitecture, branched DNA was built up from ssDNA, which could assemble into different arm junctions in a highly controlled fashion.
…”
mentioning
confidence: 99%
“…Au and Ag NCs in particular have attracted tremendous interest because of their wide applications in single-molecule studies, sensing, biolabeling, catalysis, and biological fluorescence imaging [7][8][9][10][11][12][13][14][15][16]. The physical and chemical properties of metal nanoclusters (MNCs) are highly dependent on their size, shape, composition, and even assembly architecture [17][18][19][20]. These clusters are composed of a few to hundreds of atoms with a size approaching the Fermi wavelength of an electron (~0.5 nm for Au and Ag), and they possess discrete molecular-like electronic energy band structures, resulting in intense light absorption and emission.…”
Section: Introductionmentioning
confidence: 99%